Effect of Partial and Total Replacement of Inorganic by Organic Microminerals Sources on the Quality of Broiler Carcasses - Lopes,Marcos (2017)
ABSTRACT Among the nutrients involved in the chicken diet, the microminerals deserve attention as they exert essential functions in the organism. These compounds can be provided in inorganic (traditional) and organic (chelate) forms. In organic form, the micromimerals can attend a new concept related to a better bio-availability. In this sense, the objective of this work was to evaluate the effect of the partial and total substitution of inorganic by organic sources of microminerals on the animal diet, assessing its concentration in the blood and liver after 21 and 40 days and also in the bones after 40 days. Moreover, the effect on the physical-chemical and sensory characteristics of the muscle after 15 days of storage at 4°C was also evaluated. The animals were divided into five treatments: 100% inorganic, 70% inorganic and 30% organic, 50% inorganic and 50% organic, 30% inorganic and 70% organic and 100% organic-chelate. It is shown that the use of organic sources of microminerals in the diet of poultry induced to an increase of its concentrations in the blood and liver, with no significant alterations in the compositions of bones, compared to the use of inorganic sources. Feed formulated using 50% of organic minerals and 50% of inorganic minerals led to similar results. The diet with organic minerals or mixture with inorganic sources results in a low lipid oxidation in the drumsticks stored at 4°C for 15 days, in comparison with those using only inorganic minerals. No sensory alterations were observed for all different treatments.